(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In effect, the private sector has a monopoly on outpatient services in rural and urban areas and controls more than half of hospital care. In addition, a significant portion of private healthcare providers lack the necessary professional qualifications to provide modern healthcare, many of whom are trained in Indian traditions such as Ayurveda, Unani, Siddha and homeopathy, or even without formal training. Unfortunately, these same providers are the ones poor people are most likely to turn to for health care, exacerbating the risks faced by this already disadvantaged population. Like the healthcare market in the United States, the healthcare sector in India is driven by supply-driven demand and continues to grow exponentially, especially through the adoption of new technology. This article aims to reveal the socio-economic profile of individuals accessing primary healthcare services in Salem district, Tamil Nadu